Non-adherence to pulmonary tuberculosis treatment: prevalence and associated factors in an urban community health center in Makassar, Indonesia - Zalsah Puteri Annisa Syahrani; Ridwan Amiruddin; Eri Wijaya; Octavio Sequeira; Bayu Satria Wiratama (Universitas Gadjah Mada, 2026)
Purpose: Non-adherence to tuberculosis (TB) treatment remains a major public health concern, contributing to drug resistance, ongoing trans- mission, and increased morbidity and mortality. This study aimed to determine the prevalence and determinants of treatment non-adherence among pulmonary TB patients at the Tamalate Public Health Center, Makassar City, Indonesia, focusing on sociodemographic, behavioral, and health-related factors. Methods: A cross-sectional study was conducted from April 2024 among 110 pulmonary TB patients selected through exhaustive sampling. Treatment adherence was measured using the Morisky Medication Adherence Scale (MMAS). Data were collected via structured interviews using KoboCollect and analyzed in Stata 14.0 using univariate and bivariate analyses (Chi-square and odds ratio). Results: Among 110 respondents, 30.0% were non-adherent. Most demonstrated poor TB-related knowledge (77.3%), low income (65.4%), and low education levels (42.7%). More than half experienced adverse drug effects (55.4%) and reported high family support (54.6%). In multivariate analysis, poor knowledge about tuberculosis remained independently associated with treatment non-adherence (aOR = 7.3; 95% CI: 2.13–25.30). Other factors, including adverse drug effects, household income, educational level, employment status, health insurance type, and family support, were not independently associated with non-adherence after adjustment. Conclusion: Treatment non-adherence in urban TB patients was primarily driven by poor tuberculosis-related knowledge, underscoring the need for strengthened, structured patient education within TB control programs.